Meningkatkan Motivasi Mencapai Makna Hidup Untuk Pulih Pada Pecandu Narkoba Di Fokus Rehabilitasi Narkoba Indonesia - Aritonang, Marsela Giovani; Johanna, Petra; Purba, Flora Liharni; Sitorus, Friyanka H.D.; Tarigan, Beby Astri (Psikologi Prima, 2024)
This study presents the results of community service to increase motivation to recover as the meaning of life in drug addicts carried out at the Indonesian Narcotics Rehabilitation Focus. The methods used in this program include psychoeducation sessions and discussions for 2 hours, then followed by clinical interview sessions for people with an addiction to reflect on their life experiences and the recovery process for 1 hour. This community service was attended by 20 residents, several students, and lecturers. The results obtained in this activity are the impact of strong internal motivation, and a positive environment is very important for recovery as the meaning of life. This program emphasizes the importance of motivation to recover as the meaning of life in living a quality and prosperous life while in rehabilitation and preparing for life outside rehabilitation. This service aims to provide insight into effective rehabilitation strategies for drug addicts who want to recover and reintegrate into society. Residents who participated in the activity felt that they received social support and were more motivated to recover.